A review on the Malaysia law for coral conservation in tourism site / Fatin Ain Azman ... [et al.] - Azman, Fatin Ain; Alias, Muhammad Albukhari; Halim, Nurul Husna; Abu Hassan, Syazwani (2011)
The aim of this study is to highlight on the issue of coral reef conservation in the tourism sites in Malaysia. The law protecting coral reef is not sufficient as it is not emphasized in the Fisheries Act 1985 (Act 317). It was found that the existing laws in Malaysia relating to the issues of enforcement are still lacking. Statutes such as the Fisheries Act 1985 (Act 317) and Tourism Industry Act 1992 (Act 482) were referred to. Besides, there are no specific guidelines in protecting coral reef in tourism sites even though tourism causes great impact on coral reefs. Malaysia is a signatory to international conventions and programmes such as the Ramsar Convention, Convention on Biodiversity Diversity (CBD), World Heritage Convention (WHC) and Convention on International in Endanger Species of Wild Fauna and Flora (CITES). By becoming a party to these conventions, Malaysia finally identified the threat of coral reefs in Malaysia and many plans have been established to handle the matter such as the National Policy on Biological Diversity. This study used the qualitative methodology i.e. library based research. Semi structured interviews were also conducted with the Marine Park Department (MPD) Malaysia as well as the Fisheries Department. To overcome the issue, it is highly recommended that there be a specific provision on coral reef as well as guidelines for marine activities with reference to tourism such as snorkeling and scuba diving.